Dimethoate and atrazine retention from aqueous solution by nanofiltration membranes - Ahmad, A.L.; Tan, L.S.; Shukor, S.R. Abd (Journal of hazardous materials, 2008)
In order to produce sufficient food supply for the ever-increasing human population, pesticides usage is indispensable in the agriculture sector to control crop losses. However, the effect of pesticides on the environment is very complex as undesirable transfers occur continually among different environmental sections. This eventually leads to contamination of drinking water source especially for rivers located near active agriculture practices. This paper studied the application of nanofiltration membrane in the removal of dimethoate and atrazine in aqueous solution. Dimethoate was selected as the subject of study since it is being listed as one of the pesticides in guidelines for drinking water by World Health Organization. Nevertheless, data on effectiveness of dimethoate rejection using membranes has not been found so far. Meanwhile, atrazine is classified as one of the most commonly used pesticides in Malaysia. Separation was done using a small batch-type membrane separation cell with integrated magnetic stirrer while concentration of dimethoate and atrazine in aqueous solution was analyzed using high performance liquid chromatography (HPLC). Four nanofiltration membranes NF90, NF200, NF270 and DK were tested for their respective performance to separate dimethoate and atrazine. Of all four membranes, NF90 showed the best performance in retention of dimethoate and atrazine in water.